Intercomparação de modelos hidrodinâmico e hidráulico no estudo de rio estuarino - Ribeiro, Rômulo Saboya (2005)
The main theme of the present work is a comparative study between the application of a hydraulic model and a hydrodynamic model, in the evaluation of the hydraulic transient ones in the estuary of Rio Cocó, in Fortaleza-CE, being considered the tide variation. The models used were the HEC-RAS version 3.1 that has high geometric precision in the calculations for section, but doesn’t deal with negative flow of tide and the model DYNHYD 5.0 that deals with tide intrusion, but it is limited to an equivalent rectangular section to represent the real geometric form of the section of interest. It was observed in the simulations accomplished that the HEC-RAS can’t describe the evolution of the tide prism inside of the estuary of the Rio Cocó, but if the objective is the determination of the envelope of maximum and minimum levels, the result is quite satisfactory and that the profiles of the line of water obtained with the lifted up topographical sections by Villela, they follow the same pattern of the profile obtained with the lifted up topographical sections by Silva, not suffering therefore, influence due to the different periods (sixteen years) of the topographical risings. As for the model DYNHYD5, this presents a larger precision in the determination of the real oscillation of water levels in the estuary and that the line of water obtained with the sections Villela, they presented an abrupt change in their behavior along the longitudinal profile of the river, differing of the profile with the sections Silva that was shown much stableer.